Artemether-lumefantrine, mefloquine and atovaquone-proguanil in the treatment of uncomplicated Plasmodium falciparum malaria in travellers: A retrospective comparative study of efficacy and treatment failures. Issue 52 (March 2023) - Grebenyuk, Vyacheslav; Stejskal, František; Nohýnková, Eva; Zicklerová, Ivana; Richterová, Lenka; Roháčová, Hana; Rozsypal, Hanuš; Trojánek, Milan
Abstract: Background: The aim of this study was to evaluate the rates of parasitaemia clearance and the prevalence of treatment failure in patients with uncomplicated Plasmodium falciparum malaria treated with artemether-lumefantrine (AL), mefloquine (MQ), and atovaquone-proguanil (AP). Method: The retrospective descriptive study included adult patients with uncomplicated P. falciparum malaria treated at the University Hospital Bulovka in Prague from 2006 to 2019. Parasitaemia clearance was estimated using a linear regression model. Results: The study included 72 patients with a median age of 33 years (IQR 27–45) and a male to female ratio of 3.2:1. Thirty-six patients (50.0%) were treated with AL, 27 (37.5%) with MQ and 9 (12.5%) with AP. The proportion of VFR and migrants was 22.2% with no significant differences among the three groups. The median time to the parasitaemia clearance was two days (IQR 2–3) in patients treated with AL versus four days in the MQ (IQR 3–4) and AP (IQR 3–4) groups, p < 0.001. The clearance rate constant was 3.3/hour (IQR 2.5–4.0) for AL, 1.6/hour (IQR 1.3–1.9) for MQ, and 1.9/hour (IQR 1.3–2.4) for AP, p < 0.001. Malaria recrudescence occurred in 5/36 (13.9%) patients treated with AL and in no patients treated with MQ or AP. Conclusions: The findings demonstrate the superior efficacy of AL compared to other oral antimalarials in early malaria treatment. However, we observed a higher rate of late treatment failure in patients treated with AL than previously reported. This issue warrants further investigation of possible dose adjustments, extended regimens, or alternative artemisinin-based combinations.